Evaluation of recurrent parathyroid carcinoma: A new imaging tool in uncommon entity - N. T. K. Thanseer; Ashwin Singh Parihar; Ashwani Sood; Sanjay Kumar Bhadada; Divya Dahiya; Priyanka Singh; Bhagwant Rai Mittal (World Journal of Nuclear Medicine)
Parathyroid carcinoma (PTC) is a rare endocrine tumor and uncommon cause for primary hyperparathyroidism.18F-fluorocholine (FCH) positron emission tomography and computed tomography (PET/CT) has shown promising results in the detection of parathyroid adenoma, though its role in PTC is undefined due to the paucity of incidence. The authors in this case report discuss the possible complimentary role of FCH PET/CT with18F-fluorodeoxyglucose PET/CT in the evaluation of the management of suspected recurrence, since this rare entity has high loco-regional and distant recurrence of the disease.